Investigating the Job Burnout Levels and Related Factors in Medical Interns of Guilan University of Medical Sciences - Mahnuosh Sadeghi; Negar Pourvakhshoori; Mohammad Rasoul Khalkhali; Abtin Heidarzadeh; Mahvash Gholamhosseinzadeh (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Introduction: Job burnout is a state of mental fatigue resulting from a person's professional life and consists of three dimensions: emotional exhaustion, depersonalization, and decreased personal accomplishment. This study was conducted with the aim of determining the levels of job burnout and its related factors in medical internship students of Guilan University of Medical Sciences. Methods: This cross-sectional analytical study involved 71 medical interns of Guilan University of Medical Sciences participating by census in 2022. The Maslach Burnout Inventory and a socio-economic status questionnaire were completed by the students. The data were analyzed using descriptive statistical tests (percentage, frequency, mean, and standard deviation) and inferential statistics tests (Chi-square and Fisher's exact test) through SPSS (version 25). The P-value < 0.05 was regarded as statistically significant. Results: Out of 71 medical interns, 47.9% of medical students were female, while 52.1% were male. The findings showed that 44.1% of female (15 individuals) and 51.4% of male (19 individuals) experienced severe burnout, and 55.9% of female (19 people) and 48.6% of male (18 people) had moderate burnout. Participants earned high scores in emotional exhaustion (76.1%), depersonalization (67.6%), and decreased personal accomplishment (26.8%). There was a significant relationship between the internship level (P=0.00), the medical school GPA (P=0.011), the pre-internship test score (P=0.003), and the father's education rate (P=0.023) and the emotional exhaustion score. There was also a significant relationship between the depersonalization score and the internship level (P=0.003). Results indicated a significant statistical relationship between variables of maternal education (P=0.026), economic status (as assessed by the student or family regarding housing prices) (P=0.047), and medical school GPA (P=0.004) and the decreased personal accomplishment dimension score. ConclusionThe results of this study showed a high level of burnout among interns, with students scoring high in emotional exhaustion and depersonalization components. Therefore, according to the results of the present study, further research on preventive interventions and strategies to mitigate exposure to burnout factors would be beneficial.